POLITENESS STRATEGIES OF THE KARONESE FAMILIES IN DELI TUA - Linda Astuti Rangkuti; Wiki Tedi Rahmawati (English Education Study Program FKIP Universitas Alwashliyah Medan, 2021)
This research dealt with politeness strategies of the Karonese Families in Deli Tua. The objective of this study was to describe types of politeness strategies of the Karonese Families. This research applied qualitative research design. The subjects were three of Karonese families who lived in Deli Tua. The subjects were divided into two groups; three subjects from parents and three subjects from children group. The instruments used to gain the data were observation and interview. There were two ways relationships that were observed; first, interaction parent to parent, second, interaction parent to child. The data were analyzed by using data reduction, data display and conclusion drawing/verification. The findings showed that the Karonese families used two types of politeness strategies which were (1) bald on record strategy and (2) positive politeness strategy, both interactions; parent to parent and parent to child. They expressed their politeness strategies by using kinship forms and pronoun. There were three reasons why they used bald on record strategy as the dominant type; first, Social Distance (D) of the speaker and hearer, second, Power (P) between them, and third, the Rank of Imposition (R)